(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article examines material and technical conditions as one of the fundamental factors influencing the effectiveness of physical and sports activities among university students in Ukraine. The scientific rationale is based on systemic, resource-pedagogical, and socio-psychological approaches. A theoretical analysis of the literature has revealed that, despite the presence of individual studies in the field of physical education, the issue of providing modern sports infrastructure—especially in regional institutions of higher education—remains underexplored. Within the empirical stage of the study, an online survey was conducted among 148 students from seven higher education institutions located in various regions of Ukraine. The analysis of the collected data allowed for identifying key aspects in the assessment of material and technical support, such as the availability of sports equipment, the technical condition of infrastructure, accessibility outside class hours, functional suitability of the environment, and its motivational relevance. The majority of respondents rated the existing conditions as insufficient, which directly affects the decline in physical activity levels and student engagement in sports life at their institutions. The article substantiates the need to move from a fragmented to a comprehensive vision of the problem of material and technical provision. The authors propose a concept of an integrated educational environment, where physical culture is viewed not only as an academic subject but also as a factor in socialization, health promotion, and the personal development of students. Promising directions for further research are outlined, including the study of best practices in resource management, digitalization of sports environments, and the involvement of youth in infrastructure development through social initiatives and partnership projects. The findings have both theoretical significances for the advancement of pedagogical science and practical implications for improving the educational environment of higher education institutions, enhancing student engagement in a healthy lifestyle, and promoting the sustainable development of university sports in Ukraine.